1999
DOI: 10.1128/jb.181.21.6670-6678.1999
|View full text |Cite
|
Sign up to set email alerts
|

Exponential-Phase Glycogen Recycling Is Essential for Growth of Mycobacterium smegmatis

Abstract: Bacterial glycogen is a polyglucose storage compound that is thought to prolong viability during stationary phase. However, a specific role for glycogen has not been determined. We have characterized SMEG53, a temperature-sensitive mutant ofMycobacterium smegmatis that contains a mutation inglgE, encoding a putative glucanase. This mutation causes exponentially growing SMEG53 cells to stop growing at 42°C in response to high levels of glycogen accumulation. The mutation inglgE is also associated with an altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 27 publications
9
52
0
Order By: Relevance
“…Glycogen is a glucose polymer with a-1,4 and a-1,6 linkages, which is accumulated by several bacteria. The accumulation of glycogen has been reported previously for other related actinomycetes, such as strains of Mycobacterium (Belanger & Hatfull, 1999) and Corynebacterium . In a previous study, we demonstrated that R. jostii RHA1 possesses key genes for accumulation of diverse storage compounds, such as triacylglycerols, wax esters, polyhydroxyalkanoates, glycogen and polyphosphate (Hernández et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…Glycogen is a glucose polymer with a-1,4 and a-1,6 linkages, which is accumulated by several bacteria. The accumulation of glycogen has been reported previously for other related actinomycetes, such as strains of Mycobacterium (Belanger & Hatfull, 1999) and Corynebacterium . In a previous study, we demonstrated that R. jostii RHA1 possesses key genes for accumulation of diverse storage compounds, such as triacylglycerols, wax esters, polyhydroxyalkanoates, glycogen and polyphosphate (Hernández et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…Our results point to a mechanism by which phosphorylation at the ETTS motif induces an intra-molecular shutdown of the regulatory properties of the protein, through a tight self-recognition of the phosphorylated N-terminal extension by the C-terminal FHA domain. The ensuing model is consistent with, and can account for, the apparent functional promiscuity of GarA in actinomycetes [8][9][10].…”
Section: Introductionsupporting
confidence: 68%
“…Thus, the carbohydrate storage in heterotrophic Euglena seemed to depend inversely on the ability of cells to duplicate. Recycling of stored carbohydrates is also apparently essential for growth in Mycobacterium smegmatis [32].…”
Section: Control Of Growth By the Carbon Sourcementioning
confidence: 99%